The Perils of Commercialism: Australia’s Example - Altbach, Philip; Welch, Anthony (International Higher Education, 2011)
International higher education has become a major income producer for Australia for more than two decades. The prime goal of internationalization was moneymaking, which resulted in creating problems in ethics, quality, and academic integrity. The recent policy change in reducing international students has affected institutions that had been too dependent upon high proportions of international enrollments. All of this is a predictable outcome of commercialism shaping international education.